Sistem Pelaporan Pelanggaran, Tata Kelola Yang Baik, dan Budaya Organisasi pada Pencegahan Kecurangan dalam Pengelolaan Keuangan Desa - Dinda Natalia, Sang Ayu Putu; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
The research aims to prove that the violation reporting system, good governance and organizational culture have an effect on preventing fraud in village financial management. The research was conducted in all villages in Badung Regency, with a total sample of 138 respondents, but 129 respondents could process data. The sample technique used is saturated sample technique, so that all members of the population are sampled. The data collection method in this study used questionnaires distributed to respondents with the criteria of being village officials as stipulated in the Regulation of the Minister of Home Affairs of the Republic of Indonesia number 114 of 2014, including village heads, village secretaries, financial officers in each village in the district. Badung. The data analysis technique used is multiple linear regression analysis. The results showed that the violation reporting system, good governance and organizational culture had a positive effect on preventing fraud in village financial management. Keywords: Whistleblowing System; Good Governance; Organizational Culture.